Impact of nickel downstreaming in North Maluku: Input-output analysis - Herawan, Jonathan; Susilo, Yuvensius Sri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
This study aims to determine and analyze the impact of downstream nickel commodity policies on the economy in North Maluku Province. Secondary data in this study also uses data on mining companies and industrial processing in North Maluku Province from the Mining and Energy Service of North Maluku Province, as data on nickel commodity resources and reserves in Indonesia. The analytical tools used are backward and forward linkage analysis; analysis of the I-O table, and the RAS method then iterates over the I-O table. Furthermore, four scenarios are used to view—the dynamic atmosphere of policy. Based on the results of this analysis, the results of scenario four, namely 10 percent of nickel reserves into an electric car downstream ecosystem and 20 percent produced into EV Batteries, are policy scenarios that the Government can see because they have a positive impact on the regional economy in North Maluku Province